Influence of abiotic factors on Horn Fly (Haematobia irritans irritans (L., 1758) (Diptera: Muscidae) abundance, and the role of native grass as a resting site in N.W. Santa Fe Province (Argentina) - Torres, Pablo R. (1996)
Fil: Torres, Pablo R.. Área de Parasitología y Enfermedades Parasitarias. Facultad de Ciencias Veterinarias. Universidad de Buenos Aires; Argentina